PENGARUH SUKU BUNGA KREDIT DAN JUMLAH KREDIT TERHADAP PERMINTAAN KREDIT USAHA RAKYAT(KUR) PERIODE 2020 - 2024 - Saputra, Riandi; Novila Sari , Pipit; Anwar, Amelia (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), 2025)
The problem of limited access to formal financing for MSMEs has become a strategic issue in the development of the national economic sector. The government responded to this condition by launching the KUR program as a low-interest financing scheme. This study aims to examine the effect of credit interest rates and credit amounts on KUR demand at PT Bank Rakyat Indonesia (Persero) Tbk Wates Padang Cermin Unit. This study uses a quantitative approach with secondary time series data for the period 2020–2024, which was analyzed through multiple linear regression. The results show that partially, credit interest rates have a negative and significant effect on KUR demand, while credit amounts have a positive and significant effect. Simultaneously, both independent variables have a significant effect on KUR demand. These findings support macroeconomic theory which states that lower interest rates encourage credit demand, and indicate that increasing credit availability also strengthens access to financing for MSMEs. This research provides practical contributions for policy makers and financial institutions in formulating a more effective and inclusive KUR distribution strategy. This research uses a limited research scope on one work unit (BRI Unit Wates Padang Cermin) so that the results cannot be generalized to the entire national BRI network using a relatively short observation period of only the last few years. . Keywords — Interest Rates, Credit Amounts, Credit Demand from Small Businesses, UMKM, BRI